2020
DOI: 10.31235/osf.io/97qa4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding drivers of change in park visitation during the COVID-19 pandemic: A spatial application of Big data

Abstract: In the spring of 2020, the COVID-19 pandemic changed the daily lives of people around the world. In an effort to quantify these changes, Google released an open-source dataset pertaining to regional mobility trends—including park visitation trends. This dataset offers vast application potential, containing aggregated information from location data collected via smartphones around the world. However, empirical analysis of these data is limited. Namely, the factors causing reported changes in mobility and the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
3
23
3
Order By: Relevance
“…The convergence of the two findings supports the generalizability of the behavioural pattern of urban residents under lenient social distancing measures. However, our result is in contrary to that from US, reporting changes in total greenspace use is largely due to seasonality not the pandemic, based on Google Mobility Report (Rice & Pan, 2020). The difference may be explained by the difference in urban and social context and data resolution.…”
Section: Interpretation and Implicationscontrasting
confidence: 99%
See 1 more Smart Citation
“…The convergence of the two findings supports the generalizability of the behavioural pattern of urban residents under lenient social distancing measures. However, our result is in contrary to that from US, reporting changes in total greenspace use is largely due to seasonality not the pandemic, based on Google Mobility Report (Rice & Pan, 2020). The difference may be explained by the difference in urban and social context and data resolution.…”
Section: Interpretation and Implicationscontrasting
confidence: 99%
“…However, empirical findings on how people use greenspaces during the pandemic remain scarce and inconclusive. Based on the Google mobility data in 111 counties in America, a study found that changes of park visit were mainly due to seasonality, not the pandemic (Rice & Pan, 2020). Yet, another study reported that the outdoor recreational activity in greenspaces increased by 291% during the lockdown in Norway based on mobile tracking app data (STRAVA) from runners and cyclists (Rice & Pan, 2020;Venter, Barton, Figari, & Nowell, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, we could not disentangle mobility changes due to the state-of-emergency declaration from a potential seasonal pattern of mobility though February-April. A recent study argued that seasonality rather than the COVID-19 pandemic caused the reported increases in park visitations in Google Mobility Reports for some Western US counties [58]. We note that our study area likely shares the same seasonality of mobility across county subdivisions, therefore, the potential impact of seasonality does not likely explain differences in mobility across study subregions.…”
Section: Discussionmentioning
confidence: 60%
“…These have posed a threat to humans' mental and physical health, as well as social cohesion and resilience (Bo et al 2020;Brooks et al 2020;Monson et al 2017;Gao et al 2020;Wu et al 2005;Xiang et al 2020). During the COVID-19 pandemic, parks and green spaces are receiving renewed attention due to their significant and irreplaceable functions, such as providing places for healthy outdoor recreation (Rice and Pan 2020;Rung et al 2011;Samuelsson et al 2020). Urban parks and green spaces have been recognized as green infrastructure that provide and deliver environmental, social, psychological and health functions and ecological services for residents.…”
Section: Introductionmentioning
confidence: 99%
“…According to Google COVID-19 Community Mobility Reports (Ritchie et al 2020b), park visitor numbers in most countries initially decreased before eventually increasing, and finally reaching levels equal to or even higher than a baseline taken as the mean value of daily park visitors between January 3rd and February 6th, 2020. Detailed analyses of the drivers contributing to changes in park visitor numbers during the COVID-19 pandemic are limited, especially at a global scale (Rice and Pan 2020). This paper therefore addressed the following research questions:…”
Section: Introductionmentioning
confidence: 99%